2013
DOI: 10.1186/1471-2334-13-267
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of intracellular Staphylococcus aureus by tigecyclin

Abstract: BackgroundIn the fields of traumatology and orthopaedics staphylococci are the most frequently isolated pathogens. Staphylococcus aureus and Staphylococcus epidermidis are known to be the major causative agents of osteomyelitis. The increasing number of multiresistant Staphylococcus aureus and resistant coagulase-negative staphylococci as a trigger of complicated osteomyelitis and implant-associated infections is a major problem. Antibiotic therapy fails in 20% of cases. Therefore the development of novel anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Assays were performed in triplicate. Intracellular invasion assays were performed to evaluate the effectiveness of rifamycins against internalized S. aureus, as previously described [33]. Briefly, osteoblasts were seeded in 24-well plates at 2 9 10 4 cells/mL and infected with S. aureus at a concentration corresponding to a multiplicity of infection of 50.…”
Section: Methodsmentioning
confidence: 99%
“…Assays were performed in triplicate. Intracellular invasion assays were performed to evaluate the effectiveness of rifamycins against internalized S. aureus, as previously described [33]. Briefly, osteoblasts were seeded in 24-well plates at 2 9 10 4 cells/mL and infected with S. aureus at a concentration corresponding to a multiplicity of infection of 50.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies investigated the effect of tigecyclin, teicoplanin, ofloxacin, and linezolid. These antibiotics—which are recommended in the treatment of osteomyelitis—have an intermediate intracellular antimicrobial effectiveness, higher than gentamicin or vancomycin and lower or equivalent to rifampicin (Kreis et al, 2013 ; Valour et al, 2015a ). Ofloxacin, daptomycin, and vancomycin were also deemed to limit intracellular SCVs emergence (Valour et al, 2015a ).…”
Section: Antibiotic Chemotherapies At S Aureus /Omentioning
confidence: 99%
“… 34 , 51 , 52 However, studies on macrophages and fibroblasts have shown that prolonged cell exposure allowed an increase in the aminoglycosides’ C/E ratio up to 2 to 4. 53 A time-dependent activity of gentamicin at 10 mg/L on S. aureus intracellular load was consequently highlighted, 54 sustained in the chronic model. 25 Because gentamicin is not able to diffuse into cells, its ability to target intracellular S. aureus could be due to infection-related pinocytosis allowing gentamicin to penetrate concomitantly in the same subcellular compartment as the bacteria.…”
Section: Pharmacokinetics and Intraosteoblastic Activity Of Antistaphylococcal Antibioticsmentioning
confidence: 95%